Advances in regulating the electron spin effect toward electrocatalysis applications - Liu Lin; Peiyuan Su; Yiting Han; Yunming Xu; Qiao Ni; Xinyue Zhang; Peixun Xiong; Zemin Sun; Genban Sun; Xuebo Chen (eScience)
Building highly reactive electrocatalysts is of great significance for addressing the energy crisis and developing green energy. Electrocatalytic reactions occur at the interface of catalysts, where the physicochemical properties of the catalyst surface play a dominant role. In particular, the electron spin behavior on the catalyst surface has a decisive impact on the catalytic reaction process. This review initially introduces the definition of electron spin and methods for spin manipulation. Furthermore, we summarize the advanced characterization methods of electron spin. Then, we review the latest research advancements on the spin effect in the oxygen reduction reaction, oxygen evolution reaction, carbon dioxide reduction reaction, and nitrogen reduction reaction. The catalytic mechanisms of spin manipulation in these four reactions are thoroughly discussed. Finally, we propose key directions for the future development of spin effects in the field of electrocatalysis. This review contributes to a deeper understanding of the micromechanisms in electrocatalytic reactions.